2016
DOI: 10.1177/0960327115626581
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of doxorubicin–induced hepatorenal toxicities with sesamin via the suppression of oxidative stress

Abstract: Hepatorenal toxicities are an important side effect of anthracycline antibiotics. The objective of this study was to determine whether sesamin (Ses) protects against acute doxorubicin (DOX)-induced hepatorenal toxicities. Rats received daily treatment with either 0.5% carboxymethylcellulose (10 mL/kg) or Ses (10, 20 and 40 mg/kg) orally for 10 days, followed by an intravenous injection at day 8 of either saline (10 mL/kg) or DOX (20 mg/kg). Hepatorenal toxicity was assessed by measuring the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…Sesame seeds and oil have been widely used in human diet as a healthy food for thousands of years (Namiki 2007, Guo et al 2016. Sesame oil has also been utilized in traditional medicine in, for example, India and the Middle East (Namiki 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Sesame seeds and oil have been widely used in human diet as a healthy food for thousands of years (Namiki 2007, Guo et al 2016. Sesame oil has also been utilized in traditional medicine in, for example, India and the Middle East (Namiki 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of patients treated with DOX will develop cardiomyopathy (Lipshultz et al 2010 ).The pathogenic mechanisms responsible for DOX-induced cardiotoxicity have not been completely elucidated. It is widely accepted that DOX-induced oxidative stress plays an important role in the pathogenesis of DOX cardiotoxicity (Guenancia et al 2015 ; Guo et al 2016 ; Szwed et al 2016 ). The quinone moiety of DOX participates in oxidation–reduction processes and promotes ROS generation through an enzymatic mechanism that utilizes the mitochondrial respiratory chain and non-enzymatic pathways that incorporate iron (Minotti et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this concern, Ito et al (2001) observed increase in the levels of ALT and AST in the serum of adriamycin administered rats. Similarly, Guo et al (2016) reported that administration of ADR at dose of 20 mg/kg increases the levels of ALT and AST. Swamy et al (2011) proved that administration of ADR for two weeks elevated the activity of serum marker enzymes ALT and AST.…”
Section: Discussionmentioning
confidence: 89%
“…Human beings have probably used medicinal plants for thousands of years for cure of their various ailments and still continue to do so (Hill, 1989). These natural products have many biologic and pharmacologic properties (Hosseinimehr, 2014). Today, it is estimated that about 80% of the world population relies on botanical preparations as medicine to meet their health needs (Ogbera et al, 2010).…”
Section: Introductionmentioning
confidence: 99%